Скіфія та еллінський світ Північного Причорномор’я в «Історії» Геродота - Скржинська, М.В. (Археологія, 1991)
У статті розглядаються структура й завдання Скіфського оповідання в «Історії» Геродота, роль греків Північного Причорномор'я в інформації про Скіфію, метод праці історика, а також наводяться докази подорожі Геродота до Нижнього Побужжя та Подніпров'я. В статье рассматривается структура и задачи Скифского рассказа в «Истории» Геродота, роль греков Северного Причерноморья в информации о Скифии, метод работы историка. Автор приводит доказательства путешествия Геродота в Скифию на основании его точных записей местного фольклора и детального ответа на все вопросы по географии и этнографии, которые историк ставил при описании разных стран. Из всех городов Северного Причерноморья Геродот не случайно избрал Ольвию местом своего пребывания в Скифии; для историка эта греческая колония оказалась наиболее подходящей с точки зрения системы ориентации того времени. Работа завершается выделением некоторых ошибок в Скифском рассказе и объяснением их происхождения. The paper deals with the structure and tasks of the Scythian story in «History» by Herodotus, the role of Greeks from the North Black Sea area in information about Scythia, the method of the historian’s work. The author gives proofs on Herodotus’ trip to Scythia basing on his accurate records of local folklore and detailed answer to all the questions in geography and ethnography put by the historian when describing different countries.
It is no coincidericS that Herodotbs had chosen Oibia as plaoe of hts residence of all the towns of the-North Black Sea area: this Greek colony proved to be most suitable for the historian from the viewpoint of the orientation system of that time. At the end certain mistakes in the Scythian story are shown, their origin explained.